Pengalaman Kader Kesehatan Jiwa dalam Program Kesehatan Jiwa Komunitas - Parti Utami (Ide Insan Kreatif, 2025)
Community mental health services are comprehensive, holistic, and comprehensive services focused on the community. The role of nurses is to plan and implement community mental health programs. Mental health cadres as potential workers in the community are an important aspect in realizing mental health programs. This study aims to explore the role of mental health cadres in community mental health programs. This study used a descriptive qualitative approach with six participants through interviews and observations. The interview guide used voice and video recordings. The results of the study were analyzed using theme analysis, which resulted in seven themes: encouragement and intention to become a cadre to answer community trust, less than optimal support from all parties, gratitude for successfully fulfilling responsibilities as a cadre, compassion for patients who receive negative stigma from the community, never giving up in carrying out duties as a cadre, believing in having a moral responsibility to help others as a field of worship, expecting concern from all parties. These findings can be the basis for information and input or suggestions as well as additional knowledge for health centers and the community that can be used as a reference for developing community mental health programsKeywords: qualitative, soul cadre, DSSJ